Gene-based antiangiogenic applications for corneal neovascularization - Liu, Siyin; Romano, Vito; Steger, Bernhard; Kaye, Stephen B.; Hamill, Kevin J.; Willoughby, Colin E. (Survey of ophthalmology, 2018)
Corneal avascularity is maintained by angiogenic privilege, an active process involving the production of higher level of angiostatic factors to offset the effect of angiogenic factors. A wide range of pathological insults to the cornea can disrupt this intricate equilibrium and promote angiogenesis and corneal neovascularization with resultant visual impairment. Corneal neovascularization is also a major risk factor for graft failure after keratoplasty. Current treatment options for corneal neovascularization are restricted by limited efficacy, adverse effects, and a short duration of action. The unique anatomical position and relative immune privilege of cornea make it an ideal tissue for gene-based therapies. Gene transfer vectors have been used to deliver or target genes involved in the pathogenesis of corneal neovascularization in animal models. Several proangiogenic and antiangiogenic factors have been targeted and assessed in experimentally induced corneal neovascularization. Antisense oligonucleotides targeting corneal neovascularization have entered human clinical trials and have not required vector delivery systems. The emergence of these RNA-based strategies heralds a new era in the management of corneal neovascularization and ocular therapeutics.